Growth hormone release during acute and chronic aerobic and resistance exercise: recent findings - Wideman, L.; Weltman, J. Y.; Hartman, M. L.; Veldhuis, J. D.; Weltman, A. (Sports Medicine, 2002)
Exercise is a potent physiological stimulus for growth hormone (GH) secretion, and both aerobic and resistance exercise result in significant, acute increases in GH secretion. Contrary to previous suggestions that exercise-induced GH release requires that a 'threshold' intensity be attained, recent research from our laboratory has shown that regardless of age or gender, there is a linear relationship between the magnitude of the acute increase in GH release and exercise intensity. The magnitude of GH release is greater in young women than in young men and is reduced by 4-7-fold in older individuals compared with younger individuals. Following the increase in GH secretion associated with a bout of aerobic exercise, GH release transiently decreases. As a result, 24-hour integrated GH concentrations are not usually elevated by a single bout of exercise. However, repeated bouts of aerobic exercise within a 24-hour period result in increased 24-hour integrated GH concentrations. Because the GH response to acute resistance exercise is dependent on the work-rest interval and the load and frequency of the resistance exercise used, the ability to equate intensity across different resistance exercise protocols is desirable. This has proved to be a difficult task. Problems with maintaining patent intravenous catheters have resulted in a lack of studies investigating alterations in acute and 24-hour GH pulsatile secretion in response to resistance exercise. However, research using varied resistance protocols and sampling techniques has reported acute increases in GH release similar to those observed with aerobic exercise. In young women, chronic aerobic training at an intensity greater than the lactate threshold resulted in a 2-fold increase in 24-hour GH release. The time line of adaptation and the mechanism(s) by which this training effect occurs are still elusive. Unfortunately, there are few studies investigating the effects of chronic resistance training on 24-hour GH release. The decrease in GH secretion observed in individuals who are older or have obesity is associated with many deleterious health effects, although a cause and effect relationship has not been established. While exercise interventions may not restore GH secretion to levels observed in young, healthy individuals, exercise is a robust stimulus of GH secretion. The combination of exercise and administration of oral GH secretagogues may result in greater GH secretion than exercise alone in individuals who are older or have obesity. Whether such interventions would result in favourable clinical outcomes remains to be established.